Trace metals transfer during vine cultivation and winemaking processes - Vystavna, Yuliya; Zaichenko, Liubov; Klimenko, Nina; Rätsep, Reelika (Journal of the Science of Food and Agriculture, 2017)
BACKGROUND: The study was focused on Zn, Cu and Pb transfer in the system of soil-grape-must-juice-wine in a Chardonnay grape variety from Ukrainian vine growing regions. The analyses of soil, grape, must, pomace, juice and wine were done at the study plot in the south-west of Crimea. RESULTS: Commercial white wines of Chardonnay from different vine growing regions in Ukraine were analysed for trace metals content. Results revealed that trace elements transfer was related to diverse Zn, Cu and Pb sources, trace metals bioavailability, their speciation and complexes during the wine making processes. The analysed commercial wines had lower Cu, Zn and Pb concentrations than wine from the Inkerman study plot. CONCLUSION: Trace metals concentrations were comparable to those in European wines and lower than limits recommended by International Organization of Vine and Wine. The tentative relationship between wine and soil was found for Zn at the study plot. The method can be used to describe the relationship between the soil and wine in other study areas. © 2017 Society of Chemical Industry.
Keywords: Vitis; Ukraine; Trace Elements; Food Handling; Fruit; Wine; Lead; Soil; zinek; víno; Zinc; olovo; ovocné a zeleninové šťávy; látky znečišťující půdu; Fruit and Vegetable Juices; stopové prvky; manipulace s potravinami; měď; Ukrajina; ovoce; půda; Soil Pollutants; Copper